The gene for theta-globin is transcribed in human fetal erythroid tissues. - Leung, S; Proudfoot, N; Whitelaw, E (1987)
A new gene like the alpha-globin gene has been identified in higher primates at the 3' end of the alpha-globin gene cluster. There is some controversy as to whether this gene, theta, is a functional globin gene or a non-functional pseudogene. The high degree of sequence conservation displayed by theta between primates and various mammals, such as horse and rabbit, suggests that this gene is functional in some species. Furthermore, theta encodes a 141-amino-acid polypeptide in sequence similar to alpha-globin and appears to possess functional RNA-processing signals. But the promoter region of theta is unlike the other globin genes because its CCAAT and ATA box sequences are displaced from the coding sequence by the insertion of a 200-base-pair GC-rich sequence. We demonstrate here the presence of theta-globin messenger RNA in human fetal erythroid tissue, but not in adult erythroid or other non-erythroid tissues. Furthermore, theta-globin mRNA is detectable in significant amounts in a human erythroleukaemic cell line. These results predict that theta-globin protein will be found in the early stages of human fetal development. Surprisingly, the promoter sequence of theta-globin does not correspond to the CCAAT and ATA box sequences of the gene but rather lies within the adjacent GC-rich sequence, resulting in a heterogeneous series of mRNA 5' ends 50-10 base pairs to 5' of the initiation codon. This type of promoter is reminiscent of that found in housekeeping genes such as adenine deaminase and hypoxanthine-guanine phosphoribosyl-transferase.